THE DEVOPS CONTINUUM: WALKING THE SHADOWY BRIDGE FROM INFORMATION SYSTEMS DEVELOPMENT TO OPERATIONS: This Article is removed due to plagiarism dispute. We found the claim of original author true and removed the article. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
This Article is removed due to plagiarism dispute. We found the claim of original author true and removed the article.